2020
DOI: 10.3389/fcell.2020.547653
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Global Progress in Authorized Advanced Therapy Medicinal Products: An Emerging Revolution in Therapeutic Strategies

Abstract: The introduction of advanced therapy medicinal products (ATMPs) to the global pharma market has been revolutionizing the pharmaceutical industry and has opened new routes for treating various types of cancers and incurable diseases. In the past two decades, a noticeable part of clinical practices has been devoting progressively to these products. The first step to develop such an ATMP product is to be familiar with other approved products to obtain a general view about this industry trend. The present paper de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 57 publications
(59 reference statements)
0
41
0
3
Order By: Relevance
“…Stem Cell Clinical Trials. Thus far, many clinical trials using MSCs have been completed, and some of the therapies, e.g., Cupistem®, Queencell®, Cartistem®, Cellgram®, Neurorata-R®, Prochymal®, Stempeucel®, and MesestroCell, have received market authorization in Korea, Canada, India, and Iran [139]. A list of worldwide clinical studies using stem cells in different phases can be found in National Institutes of 2).…”
Section: Stem Cells and Secretome Clinical Trialsmentioning
confidence: 99%
“…Stem Cell Clinical Trials. Thus far, many clinical trials using MSCs have been completed, and some of the therapies, e.g., Cupistem®, Queencell®, Cartistem®, Cellgram®, Neurorata-R®, Prochymal®, Stempeucel®, and MesestroCell, have received market authorization in Korea, Canada, India, and Iran [139]. A list of worldwide clinical studies using stem cells in different phases can be found in National Institutes of 2).…”
Section: Stem Cells and Secretome Clinical Trialsmentioning
confidence: 99%
“…Therein, many bioengineered solutions have been proposed (e.g., Allox ® , Epicel ® , OrCel ® , ReCell ® , Apligraf ® , TransCyte™, Lyphoderm ® ) for burn wounds, with the objective of combining traditional surgical management with novel regenerative solutions, to optimally stimulate resurgence of normal tissue structure and function [40][41][42][43][44][45]. Despite high interest and considerable development efforts, commercialization rates of such complex biological products remain relatively low [46][47][48].…”
Section: Current Clinical Need For Effective Burn Wound Early Coverage Solutionsmentioning
confidence: 99%
“…Therefore, similar to other domains of regenerative medicine, the origin and processing of the considered therapeutic cellular materials are often limiting factors in the effective development of novel therapies or products, mainly due to safety, consistency, sustainability, or manufacturing cost issues [93][94][95][96][97][98][99]. Adequately isolated lung tissue-derived progenitors (e.g., FE002-Lu cell types) constitute prime developmental candidates Appropriate cell-based product formulations are considered for local delivery in view of obtaining potential anti-inflammatory or tissue modulation effects during recovery.…”
Section: Potential Therapeutic Applications Of Diploid Lung Progenitors In Respiratory Tract Regenerative Medicinementioning
confidence: 99%